PENGARUH RELIGIUSITAS DAN LOVE OF MONEY TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Amir Hidayatulloh; Sartini Sartini (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
The objective of this study was to determine whether there is effect of religiosity and love of money on the ethical perceptions of students. The population this study is accounting students. The sampling technique uses purposive sampling, with criteria of accounting students sitting in sixth, seventh, eighth, and soon semester. This is because sixth, seventh, eight, and so on semester students who are close to the world of work. The sample of this study amounted to 230 students. This study uses survey techniques in data collection. This study uses SPSS analysis tools. This study obtained results that religiosity and love of money have no effect on student’s ethical perceptions. Keywords: Love of Money, Religiosity, Student’s Ethical Perceptions